Pro-inflammatory role of neutrophils populations in trauma patients: monitoring neutrophil populations - Vlková, Marcela; Štíchová, Julie; Surá, Karolína; Dvořáková, Karolína; Kunčický, Vojtěch; Papatheodorou, Ioanna; Blažková, Gabriela; Tomášiková, Zuzana; Bendíčková, Kamila; Dohnálková, Ludmila; Mýtniková, Alexandra; Žák, Jan; et al. (Frontiers in Immunology, 2025)
BackgroundTrauma is a leading global cause of mortality, and systemic inflammatory response syndrome (SIRS) remains a significant complication, contributing to adverse outcomes. Neutrophils, as first responders to tissue injury, undergo substantial phenotypic and functional changes following trauma. This study investigates neutrophil subpopulations defined by CD16 and CD62L expression in trauma patients, focusing on their correlation with clinical biomarkers, trauma severity, and functional properties.MethodsWe included 50 non-infectious trauma patients, categorized into SIRS and Non-SIRS groups, and 43 elective surgery patients as controls. Neutrophil subsets were analyzed at two time points (TP1 and TP2) using flow cytometry. Functional assays evaluated phagocytosis, oxidative burst, mitochondrial function, and degranulation. Correlations between neutrophil subpopulations and clinical markers, including lactate, creatine kinase, Injury Severity Score, and Trauma and Injury Severity Score, were examined.ResultsPatients with SIRS exhibited higher proportions of banded neutrophils and CD16lowCD62Llow neutrophils at TP1, alongside reduced levels of mature neutrophils. Elevated lactate and creatine kinase levels positively correlated with banded neutrophils and CD16lowCD62Llow neutrophils, while negatively correlating with mature neutrophils CD16highCD62Lhigh and hypersegmented neutrophils CD16highCD62Llow. Hypersegmented neutrophils were more prevalent in Non-SIRS patients at TP1 and in SIRS patients at TP2. Banded neutrophils showed a positive correlation with Injury Severity Score and an inverse correlation with Trauma and Injury Severity Score (TRISS), whereas hypersegmented neutrophils were negatively associated with ISS and positively correlated with TRISS. These correlations likely reflect the pro-inflammatory role of banded neutrophils and the inflammation-resolving function of hypersegmented neutrophils. CD16lowCD62Llow neutrophils displayed impaired phagocytosis, oxidative burst, and degranulation capacity, indicating functional deficiencies.ConclusionThis study highlights the dynamic changes in neutrophil subpopulations in trauma and their association with systemic inflammation and clinical severity. Increased banded neutrophils correlate with SIRS and metabolic stress, whereas hypersegmented neutrophils may contribute to resolving inflammation. CD16lowCD62Llow neutrophils exhibit functional impairments, warranting further investigation. Monitoring neutrophil subpopulations could aid in identifying trauma patients at risk for non-infectious SIRS and guide therapeutic interventions.